Menyikapi Nusyuz dalam Keluarga: Ikhtiar Mewujudkan Keluarga Harmonis (Studi Komparasi Pendapat Imam Syafi'i dan Hanafi) - Saibatul Hamdi; Ahya Ulumiddin (Al-Mudarris, 2019)
This study discusses the wife's disobedient behavior towards her husband. This rebellious behavior called nusyuzas mentioned in the Qur'an in An-Nisa verse 34. This study is important to discuss because the present-day reality shows that many family cases are not harmonious due to the wife who is disobedient to her husband. This study aims to describe the concept of nusyuzaccording to the Qur'an and also interpreted by Imam Shafi'i and Hanafi. In addition, it also aims to understand the criteria of nusyuzand the way to solve nusyuzin the Qur'an and in the view of Imam Shafi'i and Hanafi. The method used is the library research, namely by examining various related references in order to obtain a conclusion about nusyuzas contained in the Qur'an. Through this study, it can be seen that: 1) Nusyuzis the injustice committed by the wife towards her husband in the form of wife disobedience, 2) The criteria of nusyuzaccording to Al-Qur'an and the opinion of Imam Shafi'i and Hanafi are women who are proud and against their husbands and 3) The completion of the wife of nusyuzis done in three ways, namely giving advice, separating the bed, and hitting it. If the three steps are unsuccessful then it need an alternative which mediation. With regard to the sequence of these stages according to Imam Hanafi it must be done in an orderly manner but according to Imam Shafi'i one may choose which steps are the most appropriate to do.